Three Attitudes of a Reflective Teacher - Nurfaidah, Sitti (Research And Innovation In Language Learning (RILL), 2018)
Reflective teaching practice in second/foreign language teaching education has been the focus of empirical studies attention since early 1990s. Despite the importance of the implementation of reflective teaching practice in the classrooms, there is still limited research on English language teaching in Indonesian context relative to the attitude of reflective teachers as revealed in their reflection. This study examined three attitudes of reflective teachers as proposed by Dewey, i.e. open-mindedness, wholeheartedness, and responsibility. They are considered as part of the keys in identifying the reflectivity state of the teacher. Data from two EFL preservice teachersâ reflection through reflective teaching journals and interview were analyzed using thematic analysis technique to identify emerging themes and to extract narratives of experience. The findings reveal that both of the preservice teachers reflected the three attitudes in their reflection indicating their development in preparing themselves into more professional teacher. This studyâs implication on language teacher education program is also discussed.Â Keywords: reflection, reflective teacher, open-mindedness, wholeheartedness, responsibility